Valuing the risk and social costs of road traffic accidents – Seasonal variation and the significance of delay costs. (July 2017) - Bardal, Kjersti Granås; Jørgensen, Finn
Abstract: By using a conventional risk model, and a time loss model for delay, the risk, severity, and social costs of road traffic accidents have been estimated on a rural transport corridor in an area with large seasonal variations. The novelty of the study lies in the comparison of the estimates between seasons, and the inclusion of delay costs when assessing the total social costs of accidents for private motor vehicles and heavy vehicles. Increasing congestion in urban areas has motivated researchers' interest in studying the cost of delays due to accidents. However, still many countries, such as Norway, do not include delay costs when estimating the social costs of road accidents. In this study, we show that these costs can constitute a significant proportion of the social costs of accidents in rural areas, particularly during winter in regions with strong seasonal variations. The delay costs on the studied road section constituted on average 10% of total annual social costs of accidents, and were nearly 70% higher than the accidents' material costs. By including these inconvenience costs, we would achieve better estimates of the social costs of accidents, which would in turn give rise to more accurate assessments of the costs and benefits of accident reduction measures, as well as measures reducing the response time when accidents happen. Many road safety measures have been aimed at reducing accidents involving death and serious injury. This analysis shows that it can also be beneficial to take measures to reduce the number of less severe accidents, particularly in rural areas where delay costs can be high when the roads are closed because of accidents. It is thus, particularly important that such costs are included in project assessment tools to ensure that rural areas do not lose the fight for road investments. Highlights: Quantifies risk, severity, and social costs of accidents in a rural, arctic context. Compares summer and winter accidents for private and heavy vehicles. Risk of minor accidents was highest in winter, in particular for heavy vehicles. Delay costs were higher than material costs and constituted 10% of total social costs. Suggests extensions of the current cost-benefit analyses to include delay costs.